Design and application of electrocardiograph diagnosis system based on multifractal theory - Chun-kai ZHANG; Ao,ZHANGJing-wang YIN; Pan-bo TIAN; Ying ZHOU; Chang-qing QI (网络与信息安全学报)
An automatic segmentation algorithm for ECG data using differential threshold method was designed,which could identify the various ECG cycles of continuous ECG data.And it could obtain the multifractal features of multiple fractal and generalize hurst index feature of ECG data,these features were used to train artificial neural network in order to classify ECG data,the accuracy of the classifier could reach 97%.An ECG diagnosis system was implemented,which can automatically identify ECG sequences that contain multiple ECG cycles,and can automatically ignore the incomplete ECG cycle data,and could annotate every cycle of ECG data.